2022
DOI: 10.3390/ani12111354
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability Challenges for Organic Broiler Chickens: A Commentary

Abstract: As organic and conventional poultry production increased in the last decade, so did consumers’ concerns, sustainability requirements, and animal welfare as well as health issues. According to Reg. EU 848/2008 on organic production, poultry must be adapted to organic outdoor systems and cope with all the regulatory constraints in terms of nutrition, health, and welfare. Adaptability must take into account the above challenges, constraints, and concerns. Chicken adaptability should not only mean being able to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…In meat sensorial attributes, juiciness is generally correlated with the meat moisture content, but also could be influenced by the meat cutting processes. In our study, the juiciest meat score was obtained from the negative control group (1), with the interpretation as least juicy from the experimental group who received inactive yeast supplements (2)(3)(4)(5)(6)(7)(8). In discordance with our results, there could be a positive effect of administrating inactive SC on broiler cooked meat quality, due to the fact that SC possesses 5 -guanosine monophosphate and 5 -inosine monophosphate enzymatic nucleases [52], that might be appropriate as flavor enhancers, featuring the supposed umami taste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In meat sensorial attributes, juiciness is generally correlated with the meat moisture content, but also could be influenced by the meat cutting processes. In our study, the juiciest meat score was obtained from the negative control group (1), with the interpretation as least juicy from the experimental group who received inactive yeast supplements (2)(3)(4)(5)(6)(7)(8). In discordance with our results, there could be a positive effect of administrating inactive SC on broiler cooked meat quality, due to the fact that SC possesses 5 -guanosine monophosphate and 5 -inosine monophosphate enzymatic nucleases [52], that might be appropriate as flavor enhancers, featuring the supposed umami taste.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the projection concerning the increased demand for broiler meat and meat products is directly affected by the consumer's choice. Recently, consumers' preferences are directed towards safe and high-quality broiler meat and meat products, often associated with slow-growing broiler breeds [2], reared in organic systems [3], obtained using an economic circular approach by introducing organic valuable waste and by-products [4].…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to analyze of biosecurity practices and antimicrobial use during the broiler grow-out period by 5 integrated broiler operations in Korea, and 66.2% of the participating farms confirmed as organic-certified. Guarino Amato and Castellini (2022) reported that the organic broiler production system operated according to precise and specific production standards are increasing worldwide. Moreover, demand for organic poultry products, a production system that reduces chemical use and emphasis on animal welfare, has increased as it is perceived to be safer and more nutritious than conventionally raised poultry ( Cobanoglu et al, 2014 ; Niggli, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modern livestock farming often seeks to maximize profits by raising animals with rapid growth rates. Broiler chickens, in particular, are often raised in high-density conditions, and these fast-growing animals are typically sensitive to environmental changes and have poor adaptability ( 14 ). Under heat stress conditions, the gastrointestinal tract experiences ischemia and hypoxia early on and recovers last, making it susceptible to damage or failure at an early stage ( 15 ).…”
Section: Introductionmentioning
confidence: 99%